Anthocyanins in health and disease - Wallace, Taylor C.; Giusti, M. Monica (Boca Raton : CRC Press, 2014)
Anthocyanins, polyphenolic compounds abundant in certain foods, are responsible for the orange-red to blue-violet hues evident in many fruits, vegetables, cereal grains, and flowers. Interest in these pigments has intensified due to their potential health-promoting properties as dietary antioxidants, as well as their use as natural dyes in a variety of products. Mechanistic studies from in vitro experiments as well as in vivo clinical trials demonstrate wide-ranging efficacy and biological activity of anthocyanins. Anthocyanins in Health and Disease presents the first comprehensive review of modern-day research on the relationship of anthocyanins to human health and disease. Written by an interdisciplinary group of distinguished scientists, this book examines the bioavailability, chemistry, metabolism, and efficacy of anthocyanins, as well as their role in protecting the body from several age- and obesity-related chronic diseases. Chapters cover the absorption, digestion, metabolism, and excretion of anthocyanins; current methodology for the assessment of anthocyanins in the blood, plasma, urine, and tissues; and anthocyanins as potent antioxidants. The book discusses health-related topics such as anthocyanins and protection against disease, including cardiovascular disease, metabolic syndrome, type-2 diabetes, and cancers of the gastrointestinal tract. It also addresses health-promoting effects of anthocyanins, namely, maintenance of normal vision and prevention of ocular pathologies, protective effects against skin aging, and their role in innate immunity and exercise. Covering a wide array of specialized knowledge, this book provides an authoritative source of information on the role of anthocyanins in health and disease, an important step toward advancing research and enhancing communication on these functional ingredients. Book jacket.
Includes bibliographical references and index.
Keywords: Anthocyanins -- Pharmacology; Anthocyanins -- Therapeutic use; Diet therapy